HLA-B5, 7, 8, 27, and 51 Antigens and Immune Thrombocytopenic Purpura: Is There an Association?. Issue 1 (January 2020) - Pezeshki, Seyed Mohammad Sadegh; Jalali, Mohammad Taha; Amin Asnafi, Ali; Jaseb, Kaveh; Saki, Najmaldin
Abstract : Background: Immune thrombocytopenic purpura (ITP) is a bleeding disorder characterized by low platelet counts in peripheral blood, impairment of thrombopoiesis in bone marrow, and risk of mild to severe bleedings. ITP can be seen among both sexes in different ages. Although definitive pathogenesis of this disorder is still ambiguous, some of risk factors for ITP are recognized, including human leukocyte antigens (HLAs). Objective: Our goal was to evaluate the possible association between HLA-B5, 7, 8, 27, and 51 antigens with ITP for the first time. We were hoping to achieve new hypothetical diagnostic/prognostic biomarkers to introduce a new subject for further studies on HLA class I antigens as possible risk factors for ITP. Materials and Methods: A total of 37 patients with ITP were included in this study. After confirmation of ITP diagnosis, peripheral blood samples were collected from them. The expression of each of HLA antigens was evaluated by standard lymphocytotoxicity technique. Results: Compared with other studied antigens, the expression of HLA-B5 and HLA-B51 was more prevalent among our patients. According to the results, 22% of patients were positive for HLA-B5 and HLA-B51. Furthermore, no significant association was found between HLAs expressions with complete blood count parameters. Conclusions: We conclude that there is an association between HLA-B5 and HLA-B51 with ITP and that they are not likely to be used as diagnostic or prognostic biomarkers. We suggest studying the association between HLA-B antigens and ITP in large-scale studies to determine whether or not there is a significant association.